MANAGEMENT OF DIAMETER GROWTH OF THE INDIVIDUAL TREE OF Araucaria angustifolia (Bert.) O. Ktze. - Nutto, Leif (2001)
In this study the potential of diameter growth of Araucaria angustifolia (Bert.) O. Ktze. at different sites in Southern Brazil was analyzed. The objectives were to obtain information for the management of this species in uneven-aged mixed stands for high value timber production focused on future crop trees. The material consisted of 400 trees of native forests and plantations growing under varying site conditions and treatments in the states of Santa Catarina, Parana and Rio Grande do Sul. The research method applied was an ex-post facto (observational) one that is based on an explorative data analysis of data taken from 16 temporary sample plots, each consisting of 25 araucarias. For each plot it was made a stem and crown distribution map. The study shows that crown width is a very good estimator for diameter growth and it is closely related to the easy measurable variable diameter at 1.30 m. This relationship was used to develop decision tools based on the management of the growing space of the individual tree. The maximum crown expansion at a given age and therefore also the maximum radial increment are strongly related to site quality. That means that site quality has to be considered as a limiting factor for the production goals in araucaria stands. Decision tools have to be adapted to these circumstances.